2011
DOI: 10.1136/annrheumdis-2011-200564
|View full text |Cite
|
Sign up to set email alerts
|

Screening for interstitial lung disease in systemic sclerosis: the diagnostic accuracy of HRCT image series with high increment and reduced number of slices

Abstract: HRCT image series with low sampling rate allow an accurate detection of ILD with very-low-radiation dose, making this approach potentially valuable for screening in patients with SSc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 16 publications
1
22
0
1
Order By: Relevance
“…A former prospective study by Winklehner et al showed that the use of a dedicated HRCT based on reduced sequential slices throughout the entire chest can detect lung fibrosis with a high diagnostic sensitivity and accuracy of both 94% with a very low radiation dose (28). Similar strategies with the aim of dose reduction in CT for other indications have also been performed by Bankier et al and de Jong et al (29,30).…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…A former prospective study by Winklehner et al showed that the use of a dedicated HRCT based on reduced sequential slices throughout the entire chest can detect lung fibrosis with a high diagnostic sensitivity and accuracy of both 94% with a very low radiation dose (28). Similar strategies with the aim of dose reduction in CT for other indications have also been performed by Bankier et al and de Jong et al (29,30).…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, the reduced HRCT may represent a powerful tool that not only allows to visualize early ILD in SSc as shown recently (28,31), but may also be a tool to quantify subtle new fibrotic changes in lung parenchyma during follow up, especially with a significantly lower radiation exposure with a 97.4% reduction of estimated effective radiation dose in our cohort with 0.041 mSv which is in a range of a conventional chest X-ray and can be considered as a screening method for early detection and early evaluation of SSc ILD increase, rather than detection of lung fibrosis alone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations